Preventive Behaviors and Seroprevalence of SARS-CoV-2 Antibodies from Natural Infection among Immigration Police Working at Don Mueang International Airport, Thailand, before the COVID-19 Vaccination Era - Techasuwanna, Ranida; Iamsirithaworn, Sopon; Photisan, Nuttawoot; Lerdsamran, Hatairat; Prasertsopon, Jarunee; Thammawijaya, Panithee; Salakij, Bhurinud; Phumratanaprapin, Weerapong; Puthavathana, Pilaipan (Outbreak, Surveillance, Investigation & Response (OSIR) Journal, 2023)
After the first wave of the COVID-19 pandemic in Thailand in 2020, there was no data related to preventive behaviors against COVID-19 infection and prevalence of previous infections among frontline immigration police, which could be used to implement health promotion and adapt preventive methods in the organization. All frontline immigration police officers working at Don Mueang International Airport, Bangkok, were invited to participate in this cross-sectional study in May 2020. The objectives were to describe their preventive behaviors and determine the prevalence of antibodies against SARS-CoV-2 using conventional neutralization assays and ELISA tests. There were 201 eligible participants. All were asked to fill in a questionnaire, which asked them to disclose their preventive behaviors against COVID-19 infection. All were tested for antibodies against SARS-CoV-2 from natural infection as vaccines were not available at that time. The most practiced preventive behaviors were wearing a mask at work and wearing a mask in daily life, while taking sick leave when suffering from respiratory symptoms was the least practiced behavior. No SARS-CoV-2 antibodies were present in any participant. Reasons for not taking sick leave, when necessary, should be investigated in further qualitative studies.